Do Emotions Matter? Positive Emotions as a Mediator Between Gamification, Discounts, and Impulse Buying Among Gen Z - Tara Ratuliu; Rina Suthia Hayu (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2025)
Purpose: This study examines the influence of gamification and price discounts on impulse purchases among Generation Z, with positive emotions as a mediating variable.Method: A quantitative approach was employed, using primary data collected through an online questionnaire distributed via social media. The sample consists of 258 Gen Z Shopee users across Indonesia. Data were analyzed using SEM-PLS with SmartPLS version 4.0.Result: Gamification significantly influences both positive emotions and impulse buying behavior. Price discounts significantly affect positive emotions but not impulse buying directly. Positive emotions have a significant impact on impulse buying and mediate the relationship between price discounts and impulse purchases. However, they do not mediate the effect of gamification on impulse buying.Practical Implications for Economic Growth and Development: The study highlights how gamification and discount strategies that evoke positive emotions can increase impulse purchases among Gen Z in e-commerce. This can enhance transaction volumes and contribute to digital economic growth. The findings offer practical insights for e-commerce businesses seeking to influence consumer behavior.Originality/Value: This study contributes original insights by identifying positive emotions as a key mediator in the relationship between gamification, discounts, and impulse buying in Gen Z. It uncovers how gamified elements—such as challenges and rewards—stimulate emotional responses that lead to impulsive purchasing, enriching the digital marketing literature within emotion-driven e-commerce contexts.